2006
DOI: 10.1016/j.jpsychires.2005.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Facial EMG responses to dynamic emotional facial expressions in boys with disruptive behavior disorders

Abstract: Based on the assumption that facial mimicry is a key factor in emotional empathy, and clinical observations that children with disruptive behavior disorders (DBD) are weak empathizers, the present study explored whether DBD boys are less facially responsive to facial expressions of emotions than normal controls. Facial electromyographic (EMG) activity in the zygomaticus major and corrugator supercilii muscle regions, and heart rate activity were studied in 22 clinically referred 8-12-year-old DBD boys and 22 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
3
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 38 publications
5
85
3
2
Order By: Relevance
“…Although previous research has reported deficient facial reactivity to angry faces in youth with DBDs, this study is the first to explore facial reactions to a sad emotion induction, which may be more relevant to empathic responding (de Wied et al, 2006). There is now reasonable agreement that the vicarious experience of anger verses sadness evokes different physiological and neurological responses.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Although previous research has reported deficient facial reactivity to angry faces in youth with DBDs, this study is the first to explore facial reactions to a sad emotion induction, which may be more relevant to empathic responding (de Wied et al, 2006). There is now reasonable agreement that the vicarious experience of anger verses sadness evokes different physiological and neurological responses.…”
Section: Discussionmentioning
confidence: 81%
“…While taking an IQ test, externalizing boys exaggerated facial expressions of anger, but not of fear or sadness (Keltner, Moffitt, & Stouthamer-Loeber, 1995). In contrast, facial mimicry of angry facial expressions is limited among boys with DBDs, suggesting that they may be deficient in their ability to identify with angry emotional states in others (de Wied, van Boxtel, Zaalberg, Goudena, & Matthys, 2006). Thus, although preliminary research suggests that facial expressions of sadness may not be impaired in youth with DBDs, no research has investigated facial sadness in these youth using tasks designed specifically to elicit sad emotional states (Keltner et al, 1995).…”
mentioning
confidence: 99%
“…Empathic personality measures were considered valid criteria with which to evaluate the presence of structural differences in emotional empathic responsiveness. Subjects could be generally divided into high or low empathic groups, and researchers showed a direct relationship between subjects' recognition skills and different degrees of empathy (Besel 2007;de Wied et al 2006). More directly, the ability to recognize emotional faces was found to be related to personal empathy.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we tested whether low-BEES subjects are less responsive to social empathic situation than high-BEES subjects, based on the assumption that people who are low in BEES are weak empathizers (de Wied et al 2006). In parallel, we considered the modulation effect of dMPFC activity in relationship with subjects' differences as indexed by BEES: prefrontal perturbation may induce a more significant effect in high-BEES subjects, since the reduced ability on face recognition may be more important for people who are more responsive to these emotional markers, as they normally do.…”
Section: Introductionmentioning
confidence: 99%
“…The facial electromyography gives information related to the affective state of subjects. A rise of zygomatic major muscle activity results in a happy facial stimuli, whereas people tend to contract corrugators supercilii in presence of angry facial stimuli [35,58,59]. The zygomatic muscle lifts up the lips to produce a smile, whereas the corrugator muscle knits the eyebrows forming a frown facial expression.…”
Section: Electromyography Activitymentioning
confidence: 99%